Financing economic development : fiscal policy for emerging countries - Bangs, Robert Babbitt (Chicago : University of Chicago Press, 1968)
This book is about legalized seizure by government of money or property, or, by another name, taxation.
Includes bibliographical footnotes.
osc 06/12/2018
Loans
Keywords: Fiscal policy; Finance; Taxation; Developing countries